Mercurial > hg > Members > kono > Proof > galois
comparison Putil.agda @ 49:8b3b95362ca9
remove (fromℕ≤ a<sa) perm is no good
author | Shinji KONO <kono@ie.u-ryukyu.ac.jp> |
---|---|
date | Sat, 22 Aug 2020 19:55:41 +0900 |
parents | ac2f21a2d467 |
children | ddec1ef4f5e4 |
comparison
equal
deleted
inserted
replaced
48:ac2f21a2d467 | 49:8b3b95362ca9 |
---|---|
124 n = suc j | 124 n = suc j |
125 plist1 : (i : ℕ ) → i < n → List ℕ | 125 plist1 : (i : ℕ ) → i < n → List ℕ |
126 plist1 zero _ = toℕ ( perm ⟨$⟩ˡ (fromℕ≤ {zero} (s≤s z≤n))) ∷ [] | 126 plist1 zero _ = toℕ ( perm ⟨$⟩ˡ (fromℕ≤ {zero} (s≤s z≤n))) ∷ [] |
127 plist1 (suc i) (s≤s lt) = toℕ ( perm ⟨$⟩ˡ (fromℕ≤ (s≤s lt))) ∷ plist1 i (<-trans lt a<sa) | 127 plist1 (suc i) (s≤s lt) = toℕ ( perm ⟨$⟩ˡ (fromℕ≤ (s≤s lt))) ∷ plist1 i (<-trans lt a<sa) |
128 | 128 |
129 data FL : (n : ℕ )→ Set where | |
130 f0 : FL 0 | |
131 _::_ : { n : ℕ } → Fin (suc n ) → FL n → FL (suc n) | |
132 | |
133 perm→FL : {n : ℕ } → Permutation n n → FL n | |
134 perm→FL {zero} perm = f0 | |
135 perm→FL {suc n} perm = (perm ⟨$⟩ˡ fromℕ≤ a<sa ) :: perm→FL {n} ( remove (fromℕ≤ a<sa) perm ) | |
136 | |
137 FL→perm : {n : ℕ } → FL n → Permutation n n | |
138 FL→perm f0 = pid | |
139 FL→perm (x :: fl) = pprep (FL→perm fl) ∘ₚ pins ( toℕ≤pred[n] x ) | |
140 | |
141 FL→iso : {n : ℕ } → (fl : FL n ) → perm→FL ( FL→perm fl ) ≡ fl | |
142 FL→iso f0 = refl | |
143 FL→iso (x :: fl) with FL→iso fl | |
144 ... | t = {!!} | |
145 | |
146 open _=p=_ | |
147 FL←iso : {n : ℕ } → (perm : Permutation n n ) → FL→perm ( perm→FL perm ) =p= perm | |
148 FL←iso {0} perm = record { peq = λ () } | |
149 FL←iso {suc n} perm = {!!} where | |
150 fl0 : {n : ℕ } → (fl : FL n ) → {!!} | |
151 fl0 = {!!} | |
152 | |
129 all-perm : (n : ℕ ) → List (Permutation (suc n) (suc n) ) | 153 all-perm : (n : ℕ ) → List (Permutation (suc n) (suc n) ) |
130 all-perm n = pls6 n where | 154 all-perm n = pls6 n where |
131 lem1 : {i n : ℕ } → i ≤ n → i < suc n | 155 lem1 : {i n : ℕ } → i ≤ n → i < suc n |
132 lem1 z≤n = s≤s z≤n | 156 lem1 z≤n = s≤s z≤n |
133 lem1 (s≤s lt) = s≤s (lem1 lt) | 157 lem1 (s≤s lt) = s≤s (lem1 lt) |